Supramolecular Shish Kebabs: Higher Order Dimeric Structures from Ring‐in‐Rings Complexes with Conformational Adaptivity - Wang, Zhenwen; Mei, Lei; Guo, Chenxing; Huang, Song; Shi, Wei‐Qun; Li, Xiaowei; Feng, Wen; Li, Xiaopeng; Yang, Cheng; Yuan, Lihua (Angewandte Chemie International Edition, 2023)
Use of abiotic chemical systems for understanding higher order superstructures is challenging. Here we report a ring‐in‐ring(s) system comprising a hydrogen‐bonded macrocycle and cyclobis(paraquat‐o‐phenylene) tetracation (o‐Box) or cyclobis(paraquat‐p‐phenylene) tetracation (CBPQT4+, p‐Box) that assembles to construct discrete higher order structures with adaptive conformation. As indicated by mass spectrometry, computational modeling, NMR spectroscopy, and single‐crystal X‐ray diffraction analysis, this ring‐in‐ring(s) system features the box‐directed aggregation of multiple macrocycles, leading to generation of several stable species such as H4G (1 a/o‐Box) and H5G (1 a/o‐Box). Remarkably, a dimeric shish‐kebab‐like ring‐in‐rings superstructure H7G2 (1 a/o‐Box) or H8G2 (1 a/p‐Box) is formed from the coaxial stacking of two ring‐in‐rings units. The formation of such unique dimeric superstructures is attributed to the large π‐surface of this 2D planar macrocycle and the conformational variation of both host and guest. Multiple 2D H‐bonded macrocycles are threaded onto a box‐like cationic cyclophane, which further assembles into higher order dimeric shish‐kebab‐like structures. Such ring‐in‐ring(s) superstructures maximize their stability through the conformational adaptivity of both host and guest.